Control center and its relationship to the perception of success for soccer players (Journal of the College of Basic Education, 2022)
This study aims to identify both, control center and comprehend the success players for the Premier clubs participating in the championship of football of the Kurdistan Region-Iraq. The research depend on the human domain represented by the Premier clubs players and the number of (196) players who participated in the championship of the Kurdistan Region of Iraq football for the football season 2009-2010 is selected. Descriptive approach has been used in a manner (relational ties) for the relevance and the nature of the research problem was chosen deliberate way, due to the availability of the research’s samples. A number of the) 14(players for each club was selected. The results indicated the absence of psychological climate appropriate and a sense of security and tranquility, which led to a failure to develop their abilities and potential self, and the fact that respondents with great effectiveness in the collection of information classification and overlap and monitor important information and exploit cognitive, and do not have the ambition and expectations educational high, and beat character control center’s outside the control center's inside of members, and the researcher recommended that the coach should be interesting in psychological part by creating psychological climate appropriate for a player during training and competition, through the training of psychological skills, and attention to increase ambitious individual sports and increase cognitive ability has through outreach programs. As well as the data were processed statistically using appropriate statistical methods, including the percentage and the arithmetic mean and standard deviation and simple correlation coefficient of Pearson.